INVENTORY MONITORING WEB APPLICATION USING THE RAPID APPLICATION DEVELOPMENT MODEL - Edric - Suryady; Johanes Fernandes Andry (Jurnal Teknoinfo, 2023)
Warehousing is an activity of a type of goods managed by a company with the aim of selling. however, the meaning of inventory can also change depending on what industry is involved in it. Cosmetic Modern is a business engaged in the field of cosmetic beauty which as a business sells products such as skincare, beauty equipment. In the activity of managing inventory data, the recording process is still carried out in a unique way, namely by using any media as a place to write, it can be cardboard, a piece of paper. with this it raises problems including inaccuracy when recording because it takes a long time and must be checked again after being recorded. As well as the business owner must deliver the note to the head of the Warehouse because the place of business and the warehouse are not in one place but outside the place of business. The purpose of this research is to help business owners to find solutions so that the processing and recording of inventory data can run simultaneously to facilitate business processes. The Rapid Application Development method, which consists of business modeling, data, business processing, application development and in the end, continuous application trials is literate with a working time of 60 until 90 days to speed up the development process by utilizing existing software or frameworks. The results of this study indicate that this warehousing management application can help and meet business needs by recording goods and knowing which category goods fall into and solving problems that commonly occur in business. With the presence of a software-based Inventory Monitoring application that moves directly, it can be connected to the inventory database connected to the modern cosmetic shop business. This application with a website system can reduce the problems of the head of the warehouse and store manager and owner in carrying out their duties to manage inventory, product data collection and final reports. Not only that, for the use of the application it is easier to see the stock of goods in stores that are related to one another, it is hoped that the Inventory Monitoring Application based on all mobile devices can be directly connected to the store's inventory database.